Is this the time for Open Science? - López-Borrull, Alexandre; Anglada, Lluís; Abadal, Ernest (Anuario ThinkEPI, 2023)
Open science is no longer just the paradigm shift toward better science but also the spirit that encompasses the new laws and strategies of science in Spain. The three authors talk about whether we can claim that it is time for open science and what it entails.
Keywords: Open science; Open access; LOSU; ENCA; Spain